1999
DOI: 10.1021/bi990746d
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bonds in the Outer Layer of Keratin Fibers Confer Higher Mechanical Rigidity:  Correlative Nano-Indentation and Elasticity Measurement with an AFM

Abstract: Nanomechanical properties of biological fibers are governed by the morphological features and chemically heterogeneous constituent subunits. However, very little experimental data exist for nanoscale correlation between heterogeneous subunits and their mechanical properties. We have used keratin-rich wool fibers as a model of composite biological fibers; a wool fiber is a simple two component cylindrical system consisting of a core cellular component surrounded by an outer cell layer and their ultrastructure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 19 publications
(28 reference statements)
3
60
0
1
Order By: Relevance
“…It has also been used to investigate the influence of film thickness on the apparent elastic modulus using a wedge shaped gelatin film sample [1185], to correlate distribution of elastic modulus over an agar gel surface to the network structure of agar fibers [1186], to measure the dependence of compressive modulus of poly(styrene-co-vinyl-benzyl-(trimethyl)-ammonium chloride) (VBTA) microspheres on the VBTA content [270], and to characterize the mechanical stiffness of the inner and outer layer of wool fibers [1187].…”
Section: Force Volume Modementioning
confidence: 99%
“…It has also been used to investigate the influence of film thickness on the apparent elastic modulus using a wedge shaped gelatin film sample [1185], to correlate distribution of elastic modulus over an agar gel surface to the network structure of agar fibers [1186], to measure the dependence of compressive modulus of poly(styrene-co-vinyl-benzyl-(trimethyl)-ammonium chloride) (VBTA) microspheres on the VBTA content [270], and to characterize the mechanical stiffness of the inner and outer layer of wool fibers [1187].…”
Section: Force Volume Modementioning
confidence: 99%
“…However, the improvement in the carbon yield achieved for the polystyrene sulphonate graed wool was only a marginal, although polyvinyl sulphonate is reported to improve the thermal stability of polyurethane foam. 24 During heating treatment, lignin and tannic acid both probably formed crosslink between carboxyl groups of amino acids of wool keratin thorough condensation reactions, which improved the thermal stability and reduced their degradation. In the case of Hercosett resin and polystyrene sulphonate-treatment, those polymers only formed a thin layer on the surface of wool bres and therefore showed limited effect on thermal stability.…”
Section: 39mentioning
confidence: 99%
“…23,24 In spite of the high carbon content of wool bre, there is scant information in the literature on the conversion of wool bre into carbon bre. Chen et al produced activated carbon powder via pyrolysis of wool bre at 280 C under a ow of nitrogen.…”
mentioning
confidence: 99%
“…10). In addition, from nano-indentation studies [9], [10], it is reported that Young's modulus of cuticle is larger than that of cortex, which is also the factor that the contribution of the cuticle is larger.…”
Section: Uv Damage After Bleach Treatmentmentioning
confidence: 99%